PENGARUH MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KINERJA GURU UNTUK MEWUJUDKAN CAPAIAN HASIL BELAJAR SISWA - Fauziah, Puji; Ijudin, Ijudin; Anisa Larasati, Retno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
MTs Al-Musaddadiyah Garut faced human resource management challenges characterized by incidental practices, unsystematic teacher evaluations, and declining student learning outcomes and motivation during the 2022-2023 period. This study aims to analyze the influence of Human Resource Management (HRM) on Teacher Performance and its impact on Student Learning Outcomes. A quantitative method with a survey approach was employed, using a saturated sample of 30 teachers. Data were analyzed using the SEM-PLS model via SmartPLS4 software. The results indicate that HRM has a positive and significant effect on Teacher Performance and a direct impact on Student Learning Outcomes. Furthermore, Teacher Performance significantly influences student achievement. These findings validate that optimal HR management is the primary key to enhancing teacher professionalism and the overall quality of madrasah graduates. Keywords: Human Resource Management; Teacher Performance; Student Learning Outcomes; Madrasah Tsanawiyah; Islamic Education Management